Potential of a mixed extract of ginger, lemongrass, turmeric and black cumin as an immunostimulatory candidate - USWAH ZILHAYA; WIDYA SARI; SYARIFAH BALQIST SYIFA; SALSABILA AL CHUSNA; ROSNIZAR ROSNIZAR (Nusantara Bioscience, 2025)
Abstract. Zilhaya U, Sari W, Syifa SB, Chusna SA, Rosnizar. 2025. Potential of a mixed extract of ginger, lemongrass, turmeric and black cumin as an immunostimulatory candidate. Nusantara Bioscience 17: 11-20. Many Indonesian herbal plants show potential as immunostimulants, capable of enhancing the immune system’s activity. Some synthetic immunomodulators are known to cause side effects, and create demand for safer and be more effective alternatives. Ginger (Zingiber officinale), lemongrass (Cymbopogon citratus), turmeric (Curcuma longa), and black cumin (Nigella sativa) are four plants recognized for their potential as immunostimulants. These plants contain metabolites such as alkaloids, terpenoids, flavonoids, phenolics, and tannins, which can enhance immune activity. This study aims to evaluate the effectiveness of mixed extracts from these plants as immunostimulants, particularly in boosting immune responses weakened by pathogens. The research employed a completely randomized design, utilizing phytochemical tests, in vitro assays, and in vivo evaluations against Staphylococcus aureus. The results demonstrated increased activity and phagocytic capacity of macrophages following treatment with extract solutions at various doses. In vitro tests with 100 ppm and 1000 ppm concentrations, as well as in vivo tests at 650 mg/kg body weight, significantly improved macrophage phagocytic activity and capacity. The mixed extract effectively enhanced the immune system.